Strategi Guru dalam Mengatasi Masalah Siswa Disgrafia di Kelas V SDN 08 Padang Panjang 1 - Thania Yugolivia; Sartono Sartono; Indah Kaysa Putri (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to identify the strategies used by the fifth-grade teacher at SDN 08 Padang Panjang 1 in addressing writing difficulties (dysgraphia) experienced by a student. Dysgraphia is a writing disorder caused by neurological abnormalities, making it difficult for children to physically express ideas in writing. This research employs a descriptive qualitative approach. Data collection techniques include teacher interviews and classroom observation. The results show that the teacher applies various strategies, such as multisensory learning (visual, auditory, kinesthetic), fine motor exercises, and personal motivational support. Collaborative support with parents and the use of engaging learning media are also implemented. The study concludes that the application of strategies tailored to the student's condition—such as strengthening writing motor skills, adjusting writing tasks, and using an individualized approach—is effective in improving the writing ability and self-confidence of students with dysgraphia.